Integration of Sensing Framework with a Decision Support System for Monitoring Water Quality in Agriculture - Siti Nadhirah Zainurin; Wan Zakiah Wan Ismail; Siti Nurul Iman Mahamud; Irneza Ismail; Nor Azlina Ab. Aziz; Juliza Jamaludin (MDPI, 2024)
Indexed by WOS/Scopus/ERA